Family history of cancer as surrogate predictor for immunotherapy with anti-PD1/PD-L1 agents: preliminary report of the FAMI-L1 study. (22nd March 2018) - Cortellini, Alessio; Bersanelli, Melissa; Buti, Sebastiano; Gambale, Elisabetta; Atzori, Francesco; Zoratto, Federica; Parisi, Alessandro; Brocco, Davide; Pireddu, Annagrazia; Cannita, Katia; Iacono, Daniela; Migliorino, Maria R; et al.
Aim: Tumors related to hereditary susceptibility seem to have an immunosensitive phenotype.Materials & methods: We conducted a multicenter retrospective study, to investigate if family history of cancer, multiple neoplasms and early onset of cancer could be related to clinical outcomes of anti-PD-1/PD-L1 therapy. Activity and efficacy data of 211 advanced cancer patients (kidney, non-small-cell lung cancer, melanoma, urothelium, colorectal and HeN), treated at seven Italian centers with anti-PD-1/PD-L1 agents, were analyzed.Results: In this preliminary report at multivariate analyses, positive family history of cancer showed a statistically significant relationship with a better objective response rate (p = 0.0024), disease control rate (p = 0.0161), median time to treatment failure (p = 0.0203) and median overall survival (p = 0.0221). Diagnosis of multiple neoplasms significantly correlates only to a better disease control rate, while interestingly non-early onset of cancer and sex (in favor of female patients) showed significant correlation with a better median overall survival (p = 0.0268 and p = 0.0272, respectively).Conclusion: This pilot study seems to individuate easily available patient's features as possible predictive surrogates of clinical benefit for anti-PD-1/PD-L1 treatments. These preliminary results need to be confirmed with a greater sample size, in prospective trials with immunotherapy.